2019
DOI: 10.1111/ggi.13751
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin/globulin ratio is associated with cognitive function in community‐dwelling older people: The Septuagenarians, Octogenarians, Nonagenarians Investigation with Centenarians study

Abstract: Aim The objective of this study was to clarify the relationship between cognitive function and the serum albumin/globulin ratio (A/G ratio) in community‐dwelling Japanese older adults. Methods Randomly extracted residents in both urban and rural parts of Japan were enrolled in this study. A total of 1827 participants with a mean age of 70 or 80 years were recruited. A venue survey method was carried out with comprehensive studies, including interviews, blood collection, physical examination and cognitive funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…Conversely, GLO has been reported to increase during chronic inflammation, which has been linked to cognitive decline (3). Serum A/G ratio, which combines ALB and GLO, has been reported to positively relate to cognitive function (22,41). Building on earlier research, it is reasonable to postulate that serum ALB and A/G ratio may serve as protective factors for cognition, while serum GLO may be a potential risk factor.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Conversely, GLO has been reported to increase during chronic inflammation, which has been linked to cognitive decline (3). Serum A/G ratio, which combines ALB and GLO, has been reported to positively relate to cognitive function (22,41). Building on earlier research, it is reasonable to postulate that serum ALB and A/G ratio may serve as protective factors for cognition, while serum GLO may be a potential risk factor.…”
Section: Discussionmentioning
confidence: 86%
“…GLO is produced by the immune system and is thought to be implicated in damage response and related to the severity of liver inflammation (21). The A/G ratio takes both ALB and GLO into account, representing a sensitive index capable of detecting abnormalities of serum proteins (22). ALT and AST are enzymes that are engaged in the transfer of amino groups of alanine and aspartate to ketoglutaric acid.…”
Section: Introductionmentioning
confidence: 99%
“…The level of blood glucose was significantly higher in the MCI group, which reflected the impairment in glucose metabolism of the participants, which is highly correlated with cognitive impairment 28 . Several studies revealed that a reduction in albumin/globulin ratio and eGFR were associated with cognitive dysfunction [29][30][31] . These data indicated that our EGAT participants with MCI were older, and had higher BP and WHR, than those in normal cognition group.…”
Section: Discussionmentioning
confidence: 99%
“…Globulin includes immunoglobulins and is associated with in ammation. The serum A/G ratio represents a medium-to long-term in ammatory status and was correlated with serum CRP levels [15]. As CRP is known to be an independent explanatory factor for the Japanese version of the Montreal Cognitive Assessment (MoCA-J) scores, similar to the serum A/G ratio, in ammation may be involved in the association between serum A/G ratio and cognitive function.…”
Section: Discussionmentioning
confidence: 98%